Effect of Heattreatment on mechanical properties of recycled Aluminum-Piston Alloy (مجلة العلوم الشاملة, 2025)
Aluminum alloys, particularly Al–Si–Cu piston alloys, are extensively used in automotive applications due to their low density, good castability, and favorable mechanical and thermal properties. In addition, recycling of Al alloys has become increasingly important as a sustainable manufacturing strategy, offering significant reductions in energy consumption, cost, and environmental impact. However, recycling Al alloys may result in changes to their microstructure and chemical composition, which could have a negative impact on their mechanical properties. Heattreatment, nevertheless might restore their properties. In the this study, consumed aluminum pistons were recycled and subjected to various heattreatment routes, including air cooling, furnace cooling, quenching, and quenching followed by artificial aging. Mechanical performance was evaluated using Vickers hardness testing, while microstructural features were examined by optical microscopy. The results show that recycling caused a reduction in hardness from 283.36 HV for the original alloy to 262.22 HV for the recycled alloy, which is attributed to copper loss and microstructural coarsening. Furnace-cooled and air-cooled conditions exhibited lower hardness values of 249.85 HV and 264.37 HV, respectively. In contrast, quenching significantly increased hardness to a maximum value of 392.34 HV, while quenching followed by aging resulted in a hardness of 277.34 HV, indicating effective precipitation strengthening. These findings illustrate that, despite the negative effects of recycling on chemical composition and hardness, appropriate heat treatment—particularly solution treatment and quenching—can restore and even enhance the mechanical properties of recycled Al–Si–Cu piston alloys. This study provides quantitative evidence supporting the feasibility of reusing recycled piston alloys in automotive applications and contributes to a deeper understanding of the relationship between recycling, heat treatment, microstructure, and mechanical performance.